Differential features of radio as a participative media - Herrera Damas, Susana (2022)
During years past, interactivity —as the audience's possibility to be on a certain way present on those communicative processes carried out by media— has been one of the most widely discussed aspects of media reality. This possibility isn't new news for radio. In fact, as mass media, radio has an exclusive series of features which stimulate, and even privilege, the incorporation of listeners in broadcast.